DISTANCE LEARNING BASED ON ELECTRONIC EDUCATION NETWORKS - Pushkaryova, T. (Journal of Information Technologies in Education (ITE), 2014)
Specific features of distance learning in Ukraine and the newest telecommunication technologies in the modern information society are revealed in the article. The importance of using distance education network to get high quality education that meets the requirements of the XXI century is emphasized. The possibilities if distance learning and teacher’s role in this process are revealed as well as requirements towards teacher’s pedagogic activity in new context. The sample of the successful electronic education network Shodennik.ua («Щоденник.ua») is given. The network is protected from external users and offers wide range of materials for people involved in the education process (teachers, children and their parents).